GABAA Receptors: Post-Synaptic Co-Localization and Cross-Talk with Other Receptors - Shrivastava, Amulya N.; Triller, Antoine; Sieghart, Werner (Frontiers in Cellular Neuroscience, 2011)
γ-aminobutyric acid type A receptors (GABAARs) are the major inhibitory neurotransmitter receptors in the central nervous system (CNS), and importantly contribute to the functional regulation of the nervous system. Several studies in the last few decades have convincingly shown that GABA can be co-localized with other neurotransmitters in the same synapse, and can be co-released with these neurotransmitters either from the same vesicles or from different vesicle pools. The co-released transmitters may act on post-synaptically co-localized receptors resulting in a simultaneous activation of both receptors. Most of the studies investigating such co-activation observed a reduced efficacy of GABA for activating GABAARs and thus, a reduced inhibition of the postsynaptic neuron. Similarly, in several cases activation of GABAARs has been reported to suppress the response of the associated receptors. Such a receptor cross-talk is either mediated via a direct coupling between the two receptors or via the activation of intracellular signaling pathways and is used for fine tuning of inhibition in the nervous system. Recently, it was demonstrated that a direct interaction of different receptors might already occur in intracellular compartments and might also be used to specifically target the receptors to the cell membrane. In this article, we provide an overview on such cross-talks between GABAARs and several other neurotransmitter receptors and briefly discuss their possible physiological and clinical importance.